2021
DOI: 10.3390/plants10102085
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Salt Tolerance in Soybean by Exogenous Boron: Intrinsic Study of the Ascorbate-Glutathione and Glyoxalase Pathways

Abstract: Boron (B) performs physiological functions in higher plants as an essential micronutrient, but its protective role in salt stress is poorly understood. Soybean (Glycine max L.) is planted widely throughout the world, and salinity has adverse effects on its physiology. Here, the role of B (1 mM boric acid) in salt stress was studied by subjecting soybean plants to two levels of salt stress: mild (75 mM NaCl) and severe (150 mM NaCl). Exogenous B relieved oxidative stress by enhancing antioxidant defense system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Likely, as a micronutrient for instance boron (B) not only perform a significant role in plant physiology and development but also provide protection in soybean against salinity (up to 150 mM NaCl). Supplemental B regulates the different physiological processes and improves the cellular structural integrity in plants under salinity, as evidence it increased shoot FW, chl content, leaf RWC, and Pro accumulation with lower EL as growth enhancement, osmotic stress mitigation, and membrane stability indicator, respectively [92]. This elevated Pro indicated B-mediated osmoregulation to enhance osmotic status (Leaf RWC) under salinity in soybean.…”
Section: Agronomic Managementsmentioning
confidence: 85%
See 1 more Smart Citation
“…Likely, as a micronutrient for instance boron (B) not only perform a significant role in plant physiology and development but also provide protection in soybean against salinity (up to 150 mM NaCl). Supplemental B regulates the different physiological processes and improves the cellular structural integrity in plants under salinity, as evidence it increased shoot FW, chl content, leaf RWC, and Pro accumulation with lower EL as growth enhancement, osmotic stress mitigation, and membrane stability indicator, respectively [92]. This elevated Pro indicated B-mediated osmoregulation to enhance osmotic status (Leaf RWC) under salinity in soybean.…”
Section: Agronomic Managementsmentioning
confidence: 85%
“…For example, soybean seedlings grown on a pot containing Salt Stress Responses and Tolerance in Soybean DOI: http://dx.doi.org/10.5772/intechopen.102835 100 mM NaCl accumulated 38% higher H 2 O 2 and caused 25% higher lipid peroxidation compared to the seedlings grown with no NaCl [91]. Exposure to salinity (6 dS m −1 ) can also raise electrolyte leakage (EL) by 69% along with 75% and 56% increase in H 2 O 2 and malondialdehyde (MDA) contents, respectively in soybean plants [92]. A similar increment of these oxidative stress markers in a dose-dependent manner of NaCl (75 and 100 mM) was also reported by Alharby et al [5].…”
Section: Oxidative Stress In Soybean Under Salinitymentioning
confidence: 99%
“…Studies have reported that H 2 O 2 , EL, and MDA increased in rice under salt stress. Salt stress increased EL in soybean by 69%, while H 2 O 2 and MDA contents increased by 75 and 56%, respectively ( Alharby et al, 2021 ). Similar results were observed in our study ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of APX encoding genes is differentially modulated by several abiotic stresses, mostly depending on duration, intensity, elicitation/induction factors, plant ages, etc. In general, plants register an upregulation in activity as a major H 2 O 2 detoxifying protein ascorbate-glutathione cycle [74]. Evidence is more pronounced where both NO-and ABA-mediated induction of APX is more common in different crop species [75].…”
Section: Enzymatic Alleviation Of Salinity: Antioxidation and Ion Seq...mentioning
confidence: 99%